2017
DOI: 10.1073/pnas.1614315114
|View full text |Cite
|
Sign up to set email alerts
|

Pathogen boosted adoptive cell transfer immunotherapy to treat solid tumors

Abstract: Because of insufficient migration and antitumor function of transferred T cells, especially inside the immunosuppressive tumor microenvironment (TME), the efficacy of adoptive cell transfer (ACT) is much curtailed in treating solid tumors. To overcome these challenges, we sought to reenergize ACT (ReACT) with a pathogen-based cancer vaccine. To bridge ACT with a pathogen, we genetically engineered tumor-specific CD8 T cells in vitro with a second T-cell receptor (TCR) that recognizes a bacterial antigen. We th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 26 publications
2
30
0
Order By: Relevance
“…Further, we showed that antitumor CD8 + T cells are shunted from the tumor site (skin) to the distant infection site (lung), resulting in decreased immunity within the tumor, thus permitting accelerated tumor growth (22). Based on these findings and inspired by the previous work of others demonstrating improved anticancer out-comes by targeting pathogens to tumors (23)(24)(25)(26)(27), we hypothesized that infection in the same tissue as the tumor (even if the pathogen were not infecting tumor cells directly) would shunt immune cells to this "shared" site of infection and tumor, and thus inflame the tumor microenvironment to reduce tumor growth and prolong host survival. To test our hypothesis, we utilized the same tumor and infection models as our previous report (22), but here, challenged C57BL/6J (B6) mice with B16-F10 melanoma via i.v.…”
Section: Active Influenza Virus Infection In the Lung Improves Outcommentioning
confidence: 63%
“…Further, we showed that antitumor CD8 + T cells are shunted from the tumor site (skin) to the distant infection site (lung), resulting in decreased immunity within the tumor, thus permitting accelerated tumor growth (22). Based on these findings and inspired by the previous work of others demonstrating improved anticancer out-comes by targeting pathogens to tumors (23)(24)(25)(26)(27), we hypothesized that infection in the same tissue as the tumor (even if the pathogen were not infecting tumor cells directly) would shunt immune cells to this "shared" site of infection and tumor, and thus inflame the tumor microenvironment to reduce tumor growth and prolong host survival. To test our hypothesis, we utilized the same tumor and infection models as our previous report (22), but here, challenged C57BL/6J (B6) mice with B16-F10 melanoma via i.v.…”
Section: Active Influenza Virus Infection In the Lung Improves Outcommentioning
confidence: 63%
“…Other similar trials are scheduled to start in 2017 in the United States. Prior vaccination with a cancer vaccine can also be used, in an attempt to "prime" rare tumor-specific T-cells [52] . Although ACT has produced remarkable results in clinical trials with melanoma and hematologic malignancies as well as with solid cancers, some deaths have occurred in the trial phases secondary to marked cytokine release ("cytokine storm", or "cytokine release syndrome") and cerebral edema [53] .…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…Our therapy, named re-energized ACT facilitates T-cell penetration and expansion inside the tumor, while reversing the immunosuppressive TME ( Figure 2). As expected, reenergized ACT provoked a strong antitumor immune reaction that led to tumor eradication in around 60% of treated mice and also mediated long-term protection [91]. Independently, another group also utilized combinatorial therapy between ACT and viral vaccination for eradication of large orthotopic solid tumors including breast cancer, sarcoma and colon carcinoma [92].…”
Section: Adoptive T-cell Therapymentioning
confidence: 76%
“…Regardless of all these advancements, ACT still fails to produce adequate clinical responses for solid tumors, which requires a robust T-cell-mediated antitumor response. To overcome several limitations simultaneously, we explored the synergistic effect of combining ACT with pathogen-boosted immunotherapy to heighten specificity and efficacy [91]. To achieve this goal, we produced dual-specific T cells that are capable of responding to both tumor and bacterial antigens, and ACT of these cells was performed while administering intratumoral bacteria vaccination.…”
Section: Adoptive T-cell Therapymentioning
confidence: 99%